“UNDER THE SAME SUN” THE ROOTS OF COSMOPOLITANISM IN STOIC WORLDVIEW - Wattimena, Reza A.A (AEGIS : Journal of International Relations, 2017)
Cosmopolitanism understands human not just merely a member of particular social cultural community, but as the citizens of the world. This notion is deeply embedded in the history of various civilizations in the world, and one of them is in ancient Greek, namely the Stoic philosophical tradition. The Stoic philosophers connect the idea of cosmopolitanism with the idea of universal law, universal justice and universal reason. All of this ideas are based on their notion of nature, which is very important for human to achieve good life. Cosmopolitanism based on this tradition can shine a new light on various global challenges, such as the refugee crisis that happened in various parts of the world.